f(x) = 6x − x2, f(6 + h) − f(6) h , h ≠ 0
![fx 6x x2 f6 h f6 h h 0 class=](https://us-static.z-dn.net/files/daf/893a25799b485fb0e4faa7d20404b815.jpeg)
The value of f(6 + h) − f(6) is 36 + 6h - g^2 - 2gh - h^2.
Given,
f(x) = 6x − x2
We need to find f(6 + h) − f(6)
We have,
f(x) = 6x − x2
Find f(6 + h)
f(x) = 6x - x^2
Putting x = 6 + h
f(6+h)
= 6(6+h) - (g+h)^2
= 36 + 6h - (g^2 + 2gh + h^2)
= 36 + 6h - g^2 - 2gh - h^2 ________(A)
Find f(6)
f(x) = 6x - x^2
f(6)
= 6(6) - 6^2
= 36 - 36
= 0 ________(B)
Find f(6 + h) − f(6)
From A and B
= 36 + 6h - g^2 - 2gh - h^2 - 0
= 36 + 6h - g^2 - 2gh - h^2
Thus the value of f(6 + h) − f(6) is 36 + 6h - g^2 - 2gh - h^2.
Learn more about evaluating function here:
https://brainly.com/question/11270390
#SPJ1